The importance of interdisciplinary communication in the process of anticipatory prescribing - Wilson, Eleanor; Seymour, Jane (Mark Allen Healthcare, 2017)
In the UK there has been a widespread introduction of ‘anticipatory prescribing’ in community based palliative care. This involves general practitioners (GPs) writing prescriptions in anticipation of them being needed and has been encouraged to try to minimise the risk of patients suffering uncontrolled symptoms and distress; a key reason why terminally ill patients are admitted to hospital in contradiction of most people's preferences. This paper presents the findings from an ethnographic study of healthcare professionals across four care homes and four community sites in two regions (East Midlands and Lancashire/South Cumbria) of the UK. Data were collected from a range of community health professionals, resulting in 83 episodes of observation and 72 interviews. Findings highlight how essential good interdisciplinary communication is to the process of anticipatory prescribing and end-of-life care. This study found that when interdisciplinary communication worked well the anticipatory prescribing process could be carried out smoothly, optimising patient care.